O cinema catástrofe como narrativa da nação estadunidense - Di Assis, Camila (2018)
Development of an investigation the extent to which the catastrophe cinema represents the American nation in its narratives. It is a cinematographic subgenre with characteristics of the genres of terror, science fiction, drama, besides others and of very specific subjects like wars, epidemics, invasions, attacks of monsters that threaten the life of the humanity in planet Earth. It was verified through a bibliographical research that the 1970s presented 56 productions, while the years 1990 were marked by 83 films, as well as it was possible to establish the concept of catastrophe cinema, its characteristics and main categories. The films with this theme were classified in: fight for survival, comedy, monsters, epidemic, alien invasion, natural disaster, terrorism, vessel/aviation, historical and war. From these classifications, a content analysis was performed to account for the cinematographic works of the subgenre under study from 2001 to 2016, and the result was 106 Hollywood films. The next step was a bibliographic study with the objective of understanding the concepts of nation, nationalism, national identity and how they are present in the United States, after also knowing the history of that country. Next, two catastrophe films were selected for film analysis, The War of the Worlds (1953) and War of the Worlds (2005). Images and dialogues were observed to understand the part of narratives in transmitting American patriotism to viewers. Subsequently, there was a comparison of Wells's book, written in 1898, with the feature films, to differentiate the historical contexts in which each work was embedded. In this way, it has been realized that catastrophic films, through their plots and scenes, depict the United States according to the period in which they were produced.